Gestational diabetes and intraoperative tubal sterilization are risk factors for high incidence of pain after cesarean delivery: a prospective observational study - Patchareya Nivatpumin (2022)
Background: Postcesarean delivery pain leads to several adverse maternal outcomes. The primary objective of this study was to determine the incidence of moderate-to-severe pain after the use of spinal morphine for cesarean delivery. The secondary aim was to identify factors influencing moderate-to-severe pain. Methods: This was a prospective observational study. The inclusion criteria were a patient age of ≥18 years, and undergoing elective cesarean delivery under spinal anesthesia with intrathecal morphine (200 mcg). Moderate-to-severe pain was defined as a numerical rating scale score of more than 3. Preoperative and intraoperative data were collected including parity, history of cesarean delivery, pregnancy-associated problem, anesthesia blockade level, level of surgeon experience, incision type, tubal sterilization or appendectomy, and peritoneum suture. Chi-squared or Fisher’s exact tests were used to examine risk factors. Multiple logistic regression was used to analyze independent factors associated with moderate to severe pain. Results: In all, 660 patients were enrolled. As 16 were subsequently removed because they met the study withdrawal criteria, data relating to 644 patients were analyzed. The incidence of moderate-to-severe pain during the first postoperative day was 451/644 patients [70.03%; 95% confidence interval (CI): 66.38–73.44%]. The median pain score [interquartile range (IQR)] was 5 (3–6), with 176/644 (27.33%) patients needing rescue analgesics. A multivariate analysis revealed that two factors were associated with moderate-to-severe pain on the first postoperative day: gestational diabetes [adjusted OR (AOR), 1.849; 95% CI: 1.068–3.203; P=0.028] and intraoperative tubal sterilization (AOR, 1.533; 95% CI: 1.060–2.218; P=0.023). A significantly higher number of patients experienced moderate-to-severe pain on postoperative Day 1 [451/644 (70.03%)] than on Day 2 [349/644 (54.19%); P<0.001]. The median pain score [IQR] on postoperative Day 2 was 4 [3–5], which was less than on Day 1 (P<0.001). Conclusions: A high incidence of moderate-to-severe postoperative pain was found after a single dose of spinal morphine for cesarean delivery. Adequate pain control is required in women at risk of postcesarean delivery pain. More studies are needed on the analgesic requirements of diabetic patients or patients who receive intraoperative tubal sterilization.